The limits of translatability - Hargreaves, Luiz Eduardo Saldanha (2002)
Analyses the issue of translatability in general terms, contrasting different concepts and theories and seeking a theoretical solution for it. Presents several concepts of translation and language with a view to establishing a starting point for the study. In the conclusion, establishes two views of translatability which can, at the same time, oppose and complement each other.